Reagent Degradation in the Synergistic Solvent Extraction System LIX®63/Versatic™10/Nonyl-4PC - Hutton-Ashkenny, M.; Barnard, K.; Ibana, Don (Taylor & Francis, 2016)
Direct solvent extraction of nickel and cobalt from nitrate-based leach liquors has become of interest due to the successful piloting of nitric acid processes for treating nickel laterite ores. The current study investigated the stability of both hydroxyoxime and nonyl-4PC (nonyl-4-pyridine carboxylate) in LIX 63/Versatic 10/nonyl-4PC under conditions relevant to the recovery of nickel and cobalt from a nitrate-based leach liquor with stripping into sulfuric acid. Nonyl-4PC increased both the rate of hydroxyoxime degradation under the pH 1.5 extract conditions required for a potential nickel–cobalt separation process and the rate of cobalt poisoning of LIX 63. Under strip conditions and the pH 4 extract conditions required for co-extraction of nickel and cobalt, nonyl-4PC did not otherwise affect the rate of hydroxyoxime loss. Additionally, the presence of nitrate anions did not increase the loss of either hydroxyoxime or nonyl-4PC. The combination LIX 63/Versatic 10/nonyl-4PC therefore appears prospective for the co-extraction of nickel and cobalt at pH 4 from nitrate-based leach liquors.